Citizenship among young people of universities of Lima. A proposal of teaching social and political history to build civic consciousness - Casalino Sen, Carlota (2017)
We start from the problem that in the country there is little level of civic consciousness, especially among young people, who lose interest in public affairs. We propose that as citizens are the result of a historical process, through education —which is the engine of progress— we can build and thus strengthen active citizenship, especially among young people. We also note that de course of History can help build civic consciousness by teaching social and political processes that show current problems that have persisted over time. This will be the manner of contributing also to close the gap between academic history and the teaching of history. Then, we define in the basic way what is citizenship and then show empirical evidence about the perceptions of some young people from three universities in Lima on this subject.